Age dynamics of the maximum alactate power of highly qualified hockey players - Shishkov, I, Yu.; Furaev, A. N.; Rybakov, V. A. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to evaluate the dynamics of maximum alactic power (MAP) as the main indicator of the speed-strength fitness of hockey players and to identify its relationship with the age of athletes.